Global‐Scale Ionospheric Tomography During the March 17, 2015 Geomagnetic Storm - F. S. Prol; T. Kodikara; M. M. Hoque; C. Borries (Space Weather)
Abstract The correct representation of global‐scale electron density is crucial for monitoring and exploring the space weather. This study investigates whether the ground‐based Global Navigation Satellite System (GNSS) tomography can be used to reflect the global spatial and temporal responses of the ionosphere under storm conditions. A global tomography of the ionosphere electron density is constructed based on data from over 2,700 GNSS stations. In comparison to previous techniques, advances are made in spatial and temporal resolution, and in the assessment of results. To demonstrate the capabilities of the approach, the developed method is applied to the March 17, 2015 geomagnetic storm. The tomographic reconstructions show good agreement with electron density observations from worldwide ionosondes, Millstone Hill incoherent scatter radar and in‐situ measurements from satellite missions. Also, the results show that the tomographic technique is capable of reproducing plasma variabilities during geomagnetically disturbed periods including features such as equatorial ionization anomaly enhancements and depletion. Validation results of this brief study period show that the accuracy of our tomography is better than the Neustrelitz Electron Density Model, which is the model used as background, and physics‐based thermosphere‐ionosphere‐electrodynamics general circulation model. The results show that our tomography approach allows us to specify the global electron density from ground to ∼900 km accurately. Given the demonstrated quality, this global electron density reconstruction has potential for improving applications such as assessment of the effects of the electron density on radio signals, GNSS positioning, computation of ray tracing for radio‐signal transmission, and space weather monitoring.